A review of U-Th-Pb ages from the Everest region - Simpson, R; Searle, M; Parrish, R (2001)
In recent years various workers have published U-Th-Pb ages obtained from rocks in the Everest region. These ages provide crucial insights into the geological processes of melting, metamorphism and faulting that have occurred in this part of the High Himalaya. We present new U-Th-Pb data from both the Rongbuk and Khumbu sides of Everest, and present this in conjunction with a review of previously published ages. Dates obtained by various teams of scientists are complimentary, allowing a precise chronology of events to be constructed. The first reported U-Pb ages are those of Schärer (1984) who documented monazite U-Pb ages of 21.9 ± 0.2 Ma and 24.0 ± 0.4 Ma obtained from the Makalu granite, just to the east of Mount Everest, and suggests that these two distinct ages mean that the apparently homogeneous Makalu granite was generated over a period of at least two million years. Schärer et al. (1986) also dated a leucogranite from Mount Everest, which was collected near Rongbuk, on the north side of the mountain. Monazite fractions yielded an age of 14.4 ± 0.6 Ma, considerably younger than those obtained at Makalu, and at Everest. Efforts then concentrated on trying to date the cross-cutting leucogranitic dykes at Rongbuk monastery, culminating in the Ar/Ar assisted conclusion of Hodges et al. (1998) that crystallisation occurred at 16.7 Ma. A more recent study of the same area by Murphy and Harrison (1999) conclude that the dykes crystallised at ∼ 16.9 Ma. This age is the same as that obtained by us from a structurally equivalent dyke to the south of Everest. The Rongbuk dates also allow constraints on the timing of motion of the South Tibetan Detachment. The age of the main Everest granite is presented by Simpson et al. (2000) as 20.5-21.3 Ma. Further leucogranite ages from sills and dykes south of Everest are presented here. Simpson et al. (2000) also present U-Pb ages from metamorphic rocks which show that ∼20 million years elapsed between initial India-Asia collision and kyanite-sillimanite grade metamorphism. Results indicate a two-phase metamorphic history, with peak Barrovian metamorphism at 32.2 ± 0.4 Ma and a later high-temperature, low-pressure event (620°C, 4 kbar) at 22.7 ± 0.2 Ma. Younger ages obtained from the High Himalayan crystallines (HHC) at Rongbuk monastery are presented here. A further age from the base of the HHC south of Lukla is also discussed. This age is close to that obtained from monazite within leucosomes of the Namche Migmatite (Viskupic and Hodges, 2000), and could lend support to suggestions of structural discontinuity between the upper and lower HHC. Alternatively, the age may suggest that high temperatures were maintained between 32 and 22 Ma, and that the metamorphism should therefore be regarded as a continuum, rather than as discrete events. The youngest U-Th-Pb ages obtained from the region are yielded by monazites within the upper lesser Himalayan rocks. Catlos (2000) reports ages as young as 10 Ma, however, it is not clear whether these ages should be taken as indicating contemporaneous motion in the Main Central thrust zone.